2003
DOI: 10.1088/0953-8984/15/29/319
|View full text |Cite
|
Sign up to set email alerts
|

M ssbauer spectroscopy and chemical bonds in BaFe12O19hexaferrite

Abstract: Barium hexaferrite was synthesized by chemical co-precipitation. Its Mössbauer spectra were obtained. A semi-empirical model, based on the Phillips theory of bonding, has been developed for quantitative explanation of the Mössbauer isomer shifts of Fe ions in BaFe12O19 crystals. The results show that, using the relationship between isomer shifts and covalency, the site assignments in hexaferrites will be resolved easily. This paper provides a powerful tool for studying other members of the hexagonal ferrimagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 15 publications
2
33
0
1
Order By: Relevance
“…Gao et al [57] reported that Fe 3 O 4 nanoparticles are partly transformed into ␥-Fe 2 O 3 after heating at 200 • C for 3 h in air and are completely transformed into ␥-Fe 2 O 3 if they are heated at 600 • C for 3 h. In order to investigate the corresponding transformation for biogenic magnetite, we took biogenic magnetite isolated from MV-1 bacteria, stripped it of its membrane with surfactant, and heated it in air at 600 • C for 3 h. Fig. 7a presents a TEM image while Fig.…”
Section: Generating Oxidized Magnetite From Magnetosomesmentioning
confidence: 99%
“…Gao et al [57] reported that Fe 3 O 4 nanoparticles are partly transformed into ␥-Fe 2 O 3 after heating at 200 • C for 3 h in air and are completely transformed into ␥-Fe 2 O 3 if they are heated at 600 • C for 3 h. In order to investigate the corresponding transformation for biogenic magnetite, we took biogenic magnetite isolated from MV-1 bacteria, stripped it of its membrane with surfactant, and heated it in air at 600 • C for 3 h. Fig. 7a presents a TEM image while Fig.…”
Section: Generating Oxidized Magnetite From Magnetosomesmentioning
confidence: 99%
“…A theory describing the chemical bond of complex crystals has been developed by Zhang et al [8][9][10][11]16,17 It have been successfully applied to the material properties. [18][19][20] Zhang 8 has pointed out that the properties of a crystal can be described by chemical bond parameters, and any complex crystal can be decomposed into different kinds of pseudo-binary crystals.…”
Section: Theorymentioning
confidence: 99%
“…Therefore, for a given crystal, it is reasonable to investigate its origin of hardness by starting from the point of view of the chemical bond. [8][9][10][11] Recently, a new definition of the hardness of covalent crystals has been presented. [12][13][14][15] This paper gives a theoretical prediction of hardness values of these crystals by using the chemical bond theory of complex crystals and hardness theory.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Phillips, Van Vechten, and Levine (PVL) [22,23] scheme, which is mainly suitable for binary crystals, a theory describing the chemical bond of complex crystals has been developed by Zhang and co-workers [14][15][16][17]. It has been successfully applied to the optical properties [24][25][26].…”
Section: Theorymentioning
confidence: 99%
“…However, mechanical properties of Ca 4 REO(BO 3 ) 3 are little investigated, although they are obviously important for all kinds of device application [7][8][9][10][11][12][13]. Therefore, this paper gives a theoretical prediction of hardness values of these crystals by using the chemical bond theory of complex crystals [14][15][16][17] and hardness theory [18][19][20][21]. It helps to further understand the other mechanical properties.…”
Section: Introductionmentioning
confidence: 99%